Eclampsia-Induced Posterior Reversible Encephalopathy Syndrome in a Donor Oocyte Recipient - Jesús Garcia Castro; Jorge Rodríguez-Pardo; Javier Díaz de Terán (Tehran University of Medical Sciences, 2021)
Objective: Posterior reversible encephalopathy syndrome (PRES) has been robustly associated with preeclampsia, hyperperfusion or endothelial dysfunction suggested as possible mechanisms. In this article, we report an illustrative case of this complication in a patient with risk factors for hypertensive disorders in pregnancy, including advanced maternal age and donor oocyte fertilization. Case report: We present a case of a 40-year-old pregnant, donor oocyte recipient with sudden decreased visual acuity accompanied by hypertension, proteinuria and tonic-clonic seizures. Magnetic resonance imaging (MRI) of the brain showed bilateral lesions in the parieto-occipital regions suggestive of vasogenic edema, leading us to suspect posterior reversible encephalopathy syndrome. The patient underwent an emergency cesarean section and labetalol and magnesium sulfate were administered intravenously. The neurological symptoms and radiological findings resolved following delivery and the patient's blood pressure normalized, supporting the diagnosis of posterior reversible encephalopathy syndrome. Conclusion: Pregnancy by donor oocyte fertilization may entail a higher risk of eclampsia and associated posterior reversible encephalopathy syndrome.